Pengaruh Pendidikan Karakter Terhadap Motivasi Belajar Siswa Kelas V SD Negeri 177055 Sigalogo Tahun Ajaran 2022/2023 - Rio Samuel Nababan; Bogor Lumbanraja; Rumiris Lumban Gaol; Reflina Sinaga; Antonius Remigius Abi (Journal on Education, 2023)
This study aims to determine the effect of character education on student learning motivation in class V SD 177055 Sigalogo Learning Year 2022/2023. In this study using quantitative methods, the population of this study was the entire fifth grade of SD 177055 Sigalogo. Sampling using simple random sampling and the sample used was 30 students. The results of this study indicate that character education affects student learning motivation. To test the hypothesis, the hypothesis test used is the t-test. The results showed that character education (X) has an average of 80.13 which is interpreted as high and learning motivation (Y) has an average value of 78.13 which is interpreted as high. The result of the correlation coefficient in this study is rxy = 0.554 with the results of hypothesis testing using the t-test obtained the results of tcount> ttable with the results of 3.520> 2.048 with a significant level (α = 0.05) then Ho is rejected and Ha is accepted, namely there is a significant influence between Character Education on Learning Motivation of Class V Students of SD 177055 Sigalogo Learning Year 2022/2023.